MEDIA KOMUNIKASI KESEHATAN UNTUK TUNA RUNGU DAN TUNA WICARA BERBASIS ANDROID - Ryan Ari Setyawan; Rizqi Mirza Fadilla (Informasi Interaktif, 2022)
This study aims to create a health communication media application that can assist communication for deaf and speech impaired patients. Health communication media that can run on Android smartphones to make it easier for health workers to communicate with deaf and speech impaired patients when visiting health facilities. The method used is agile development software development method. This method was chosen because of the methods and methodologies that make all personnel in the team work efficiently, think more effectively and make better decisions. For software testing using usability testing. Usability testing was chosen because it is one of the categories of methods in usability evaluation that observes users of a design and then takes data and analyzes it.The results of these trials are that the application has no bugs or errors and the results of usability testing show all ratings above 74%. The usability assessment shows that the application can be well received by users, namely health workers as a means of communication for patients with special needs.Keywords : Agile Development, Android, Media Komunikasi Kesehatan, Usability Testing.